What makes us satisfied (or not) at work? - Groff, Brandon (University of Wisconsin--Stout, 2018)
Since the increase in the utilization of technology, organizations have more sedentary employees. Increased physical activity can help individuals lead healthier lives and improve mental health such as less depression, anxiety, and stress. Therefore, organizations should seek to use this information to improve the health of their employees. Exercise has also shown to be positively associated with job satisfaction which has many robust findings for organizational-outcomes (e.g. less turnover, better performance). The purpose of this study is three-fold: 1) to examine if exercise is related to job satisfaction, 2) to determine if exercise can predict job satisfaction more than constructs such as job involvement, organizational commitment and stress, and 3) to determine if exercise intensity is important in predicting job satisfaction. A sample of 186 fulltime workers from University of Wisconsin-Oshkosh completed an online Qualtrics survey that contained questions about job satisfaction, physical activity, organizational commitment, job involvement, perceived stress, and basic demographic questions. Results showed that total exercise was negatively correlated with job satisfaction, and organizational commitment and perceived stress predicted job satisfaction in the expected direction. However, neither job involvement, total exercise or exercise intensity predicted job satisfaction.
Keywords: Exercise; Employees; Job satisfaction; University of Wisconsin--Oshkosh